Use of glycine in food products - Strashynskyi, Igor; Marynin, Andriy; Hrytsai, Maksym; Polishchuk, Iryna (My University, 2021)
When assessing the quality of food products, special attention is paid to their taste and aroma. Nutrition physiology considers taste and flavoring substances as important components of food that improve digestion by activating the secretion of digestive glands and contribute to the health improvement of intestinal microflora.
Keywords: кафедра технології м’яса і м’ясних продуктів; glycine; glucose; food industry